2021
DOI: 10.1093/jisesa/ieab012
|View full text |Cite
|
Sign up to set email alerts
|

Brown Stink Bug (Hemiptera: Pentatomidae) Damage to Seedling Corn and Impact on Grain Yield

Abstract: Brown stink bugs, Euschistus servus, are an important early-season pest of field corn in the southeastern United States. Feeding in the early stages of corn development can lead to a number of growth deformities and deficiencies and, ultimately, a reduction in yield. An observational and two experimentally manipulated trials were conducted in 2017 and 2018 to 1) determine optimal timing for assessing brown stink bug damage, 2) assess the level of damage from which yield compensation can occur, and 3) examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…3(D)), induce development of tillers or abortion of seedlings, and therefore, decrease corn yield. 18,45 The severity of D. furcatus damage at the seedling stage is related to the intensity of the effects on yield components, such as height of plants, stem diameter and number of seeds produced. 46 It has been reported that heavy infestations of this stink bug can reduce yields by up to 50% in Brazilian and Argentine corn fields.…”
Section: From Secondary Pest Of Soybean To a New Pest Of Cornmentioning
confidence: 99%
See 4 more Smart Citations
“…3(D)), induce development of tillers or abortion of seedlings, and therefore, decrease corn yield. 18,45 The severity of D. furcatus damage at the seedling stage is related to the intensity of the effects on yield components, such as height of plants, stem diameter and number of seeds produced. 46 It has been reported that heavy infestations of this stink bug can reduce yields by up to 50% in Brazilian and Argentine corn fields.…”
Section: From Secondary Pest Of Soybean To a New Pest Of Cornmentioning
confidence: 99%
“…46 It has been reported that heavy infestations of this stink bug can reduce yields by up to 50% in Brazilian and Argentine corn fields. 23,43,46,47 Although adults of D. furcatus in Argentina and Brazil, and similarly Euchistus servus in USA, feed on corn seedlings, 45 after a short period of time they leave the corn field to look for alternative hosts, thus suggesting that seedlings are not the most appropriate food source for these stink bugs. Feeding bioassays under laboratory conditions has shown that D. furcatus adults feed on corn seedlings for only 2 h. 20 Noteworthy, there is no record about D. furcatus depositing their eggs or nymphs completing their development on corn seedlings.…”
Section: From Secondary Pest Of Soybean To a New Pest Of Cornmentioning
confidence: 99%
See 3 more Smart Citations